Respuesta :

-86 = -6(-3p - 3) - 5p

Distribute the -6 into the parentheses:

-86 = (-6 * -3p) + (-6 * -3) - 5p

-86 = 18p + 18 - 5p

Simplify:

-86 = 13p + 18

Subtract both sides by 18:

-86 - 18 = 13p + 18 - 18

-104 = 13p

Divide both sides by 13:

[tex]\frac{13p}{13}[/tex] = [tex]\frac{-104}{13}[/tex]

[tex]\frac{p}{1}[/tex] = [tex]\frac{-8}{1}[/tex]

p = -8

Good luck! If you have any questions, don't be afraid to ask :))

-T.B.

Answer:

Step-by-step explanation:

First you distribute( multiply) the -6 to everything inside the parentheses.

Now you have -86= 18p + 18 - 5p

Now combine like terms

-86 = 13p + 18

Now subtract 18 from both sides of the equal sign

-104 = 13p

Now divide by 13 on both sides of the equal sign.

p = -8

ACCESS MORE